Action Civics for Promoting Civic Development: Main Effects of Program Participation and Differences by Project Characteristics. Issue 3 (December 2016) - Ballard, Parissa J.; Cohen, Alison K.; Littenberg‐Tobias, Joshua
Abstract: Using both quantitative and qualitative data, this study examined the effect of participating in an action civics intervention, Generation Citizen (GC), on civic commitment, civic self‐efficacy, and two forms of civic knowledge. The sample consisted of 617 middle and high schools students in 55 classrooms who participated, or were soon to participate, in Generation Citizen. Hierarchical linear models revealed that participating in Generation Citizen was associated with positive gains in action civics knowledge and civic self‐efficacy. Qualitative coding identified three types of project characteristics that captured variability in the action projects student chose to complete: context, content, and contact with decision makers. Interactions between project characteristics and participation in GC revealed differences in civic outcomes depending on project characteristics.